Alkylated Meso‐Macroporous Metal–Organic Framework Hollow Tubes as Nanocontainers of Octadecane for Energy Storage and Thermal Regulation. Issue 35 (2nd August 2018) - Tang, Jia; Chen, Xingyu; Zhang, Liguo; Yang, Mu; Wang, Peng; Dong, Wenjun; Wang, Ge; Yu, Fang; Tao, Jinzhang
Abstract: Alkylated meso‐macroporous Cr‐MIL‐101 hollow tubes (ACHT) are synthesized through the coordination of Cr 3+ with alkylated bridged ligands. The alkylated ligands work as both bridging ligands and structure‐directing agents, which presents a new strategy for synthesizing meso‐macroporous metal–organic frameworks (MOFs). This is the first example of 1D meso‐macroporous MOF hollow tubes with large pore diameter (5–136 nm). Furthermore, the octadecane@ACHT form‐stable phase change materials (FSPCMs) are prepared using ACHT as nanocontainers for octadecane. The nanocavity of ACHT possesses enough storage space for octadecane, and the large number of alkyl chains on the ACHT framework induces octadecane molecules to crystallize from α‐ to β‐crystals. Considering the comfortable phase transition temperature (27.7 °C) and the relatively large thermal storage capacity (187 J g −1 ), the octadecane@ACHT FSPCMs can be used in interior wall of building to improve the indoor thermal comfort or in the field of thermal‐regulated textiles and clothing. Abstract : Meso‐macroporous metal–organic framework hollow tubes are successfully prepared by a facile approach using alkylated bridged ligands as both bridging ligands and a structure‐directing agent strategy. The obtained alkylated meso‐macroporous Cr‐MIL‐101 hollow tubes as nanocontainers with large pore diameter (5–136 nm) are used to store octadecane for novel form‐stable phase change materials, which possess high energy storage and thermal regulation capacity.